How do university students perceive the educational transition in the COVID-19 era: A cross-sectional study from 15 Arab countries - Eltewacy, Nael Kamel; Abu Farha, Rana K.; Matar, Sajeda G.; Jobran, Afnan W. M.; Nagi, Nesma Gebril; Benmelouka, Amira Yasmine; Rohim, Hagar Ismail; Yasseen, Enas M.; Ayman, Omnia; El-Din Sayed, Aya N.; Abdallah, Reem Ahmed M.; Abdallah, Rana Ahmed M.; et al. (John Wiley & Sons, 2023)
Background and Aims The viral agent of the novel coronavirus disease 2019 (COVID-19) continues to spread worldwide, leading to a global pandemic. this may negatively affect students' mental health who have to maintain their learning efforts. Therefore, we aimed to assess students' perceptions of the online learning programs designed for university students in Arab countries during the COVID-19 pandemic. Methods This cross-sectional study was conducted on university students using a self-administered online questionnaire in 15 Arab countries, including 6779 participants. The actual sample size was calculated using the EpiInfo program calculator. The validated, piloted questionnaire assessed the effectiveness of internet-based distance learning applications used in these countries during the pandemic. The SPSS version 22 was used. Results Among the 6779 participants, 26.2% believed that their teachers diversify learning methods, 22.0% thought that their teachers were able to treat the weakness the students have, and 30.7% agreed that their teachers efficiently communicate with them through COVID-19 internet-based learning process. Around 33% of students participated in lectures effectively, 47.4% submitted their homework within accepted deadlines, and 28.6% thought that their colleagues did not cheat during exams and homework. Around 31.3% of students believed that online-based learning had a role in directing them towards research, and 29.9% and 28.9%, respectively, believed that online learning had a role in developing analytical thinking and synthesis skills. Participants reported many suggestions to enhance the process of internet-based distance learning in the future. Conclusion Our study suggests that online-based distance learning in Arab countries still needs more improvement as students still are more inclined toward face-to-face teaching. However, exploring the factors that influence students' perceptions of e-learning is vital for improving the quality of online-based distance learning. We recommend exploring the perceptions of educators regarding their experience towards online-based distance learning during COVID-19 lockdown.